1996
DOI: 10.1083/jcb.135.4.1009
|View full text |Cite
|
Sign up to set email alerts
|

Plakophilins 2a and 2b: constitutive proteins of dual location in the karyoplasm and the desmosomal plaque.

Abstract: Abstract. Using antibodies and recombinant DNA techniques, we have identified plakophilin 2, a novel desmosomal plaque protein of Mr 100,000 (estimated from SDS-PAGE), which is a member of the arm-repeat family of proteins and can occur in two splice forms (2a and 2b) because of the insertion of a 44 amino acid (aa)-encoding exon. In its aa sequence (837 and 881 aa, calculated pls: 9.33 and 9.38, mol wts 92,750 and 97,410 kD), it is conspicuously related to the 80-kD plakophilin 1, with which it shares a centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
292
1
2

Year Published

1997
1997
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 265 publications
(302 citation statements)
references
References 69 publications
7
292
1
2
Order By: Relevance
“…At least three groups of molecules contribute to the formation of desmosomes: desmosomal cadherins, armadillo-repeat proteins and plakins 7 . The plakophilins, which are armadillo-related proteins, contain ten 42-amino acid armadillorepeat motifs and are located in the outer dense plaque of desmosomes linking desmosomal cadherins with desmoplakin and the intermediate filament system 8 . Like other armadillo-repeat proteins, plakophilins are also found in the nucleus, where they may have a role in transcriptional regulation 9 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At least three groups of molecules contribute to the formation of desmosomes: desmosomal cadherins, armadillo-repeat proteins and plakins 7 . The plakophilins, which are armadillo-related proteins, contain ten 42-amino acid armadillorepeat motifs and are located in the outer dense plaque of desmosomes linking desmosomal cadherins with desmoplakin and the intermediate filament system 8 . Like other armadillo-repeat proteins, plakophilins are also found in the nucleus, where they may have a role in transcriptional regulation 9 .…”
mentioning
confidence: 99%
“…Like other armadillo-repeat proteins, plakophilins are also found in the nucleus, where they may have a role in transcriptional regulation 9 . Plakophilin-2 exists in two alternatively spliced isoforms (2a and 2b), interacts with multiple other cell adhesion proteins and is the primary cardiac plakophilin 8,10 .…”
mentioning
confidence: 99%
“…For dg (c), this association was much weaker, and for dp (b) no such correlation was found. d, survival rates in stage IV tumors in relation to ecad protein scores (Ͻ5 vs. [5][6][7][8]. Note that ecad was a strong prognostic marker of stage IV tumors.…”
Section: Statistical Analysis Of the Clinical Relevance Of The Ihc Exmentioning
confidence: 99%
“…The "classical" E-cadherin (ecad) maintains intercellular adhesion in the adhaerens junction, and the desmogleins (dg) and desmocollins (dc) are the principal cadherins of the desmosomes. [3][4][5][6][7][8][9][10][11][12][13] Regarding adhaerens junctions, numerous studies have shown that loss of adhesion can be caused by deletions or mutations, 14 -17 silencing by CpG methylation 18 -20 or otherwise altered gene expression, resulting in loss or reduction of protein staining of 1 of the proteins involved in junction formation [21][22][23] ; (for reviews, see references 24,25). From these studies, it was concluded that alteration of cellular adhesion may lead to dedifferentiation, tumorigenesis and metastasis.…”
mentioning
confidence: 99%
“…In the experiments reported here, antibodies NOH61-2.1 and NOH61-5.1 directed against the peptide sequences GPKGDKASDPEAGV (aa 332-345) and EKLKTYFEDNPRDLQ (aa 458 -472), respectively, were routinely used after affinity purification on iodoacetyl-immobilized peptide (Mertens et al, 1996). Antibody NOH61-4.2 (aa 23-36; TDL-GWSRPTLIQEK) showed the same specificities.…”
Section: Generation Of Peptide-specific Antibodies Against the Human mentioning
confidence: 99%